Integrated Care for Pregnant Women and Parents With Methamphetamine-Related Mental Disorders - Petzold, Johannes; Spreer, Maik; Krüger, Maria; Sauer, Cathrin; Kirchner, Tobias; Hahn, Susanna; Zimmermann, Ulrich S.; Pilhatsch, Maximilian (Frontiers in Psychiatry, 2021)
Background: Methamphetamine use is a rapidly increasing cause of morbidity and mortality. Pregnant women and new parents who consume methamphetamine are at high risk since they seldom seek health services despite having multiple needs. We addressed this care gap by implementing an easily accessible program that pools resources from psychiatric, obstetric, and pediatric departments as well as community and government agencies. Method: This real-life observational study evaluated an integrated care program in 27 expecting parents and 57 parents of minors. The outcome criteria were treatment retention, psychosocial functioning, and abstinence. We compared participant demographics according to outcome and applied ordinal logistic regression to predict treatment success. Results: Patients received integrated care for almost 7 months on average. Nearly half achieved stable abstinence and functional recovery. Only one pregnant woman dropped out before a care plan could be implemented, and all women who gave birth during treatment completed it successfully. Three-fourths of patients had psychiatric comorbidities. Patients with depressive disorders were almost 5 times less likely to succeed with treatment. Attention-deficit hyperactivity disorder (ADHD) was diagnosed in nearly 30% of patients who dropped out of a care plan, which was about 4 times more often than in the successful outcome group. Conclusion: Our program engaged pregnant women and parents in treatment and helped them recover from methamphetamine-related mental disorders. Management of comorbid ADHD and depression should be an integral part of care initiatives to counter the methamphetamine crisis that affects parents and children across the globe.